Lack of effect of intermittent preventive treatment for malaria in pregnancy and intense drug resistance in western Uganda - Vera, Braun; Rubaihayo, John; Tumwesigye, Nazarius Mbona; Frank, P. Mockenhaupt (Malaria Journal, 2015)
Intermittent preventive treatment in pregnancy (IPTp) with sulfadoxine–pyrimethamine (SP) is widely implemented in sub-Saharan Africa for the prevention of malaria in pregnancy and adverse birth outcomes. However, in areas of intense SP resistance, the efficacy of IPTp may be compromised.